Handbook of Exoplanets (Springer International Publishing, 2018)
This state-of-the-art reference work includes over 15 sections dealing with all aspects of exoplanets and exobiology research, including historic aspects, the Solar System as a template, objects at the planet-to-star transition, exoplanet detection and characterization with related instrumentation, technology and software tools, planet and planet-system statistics with recent and planned surveys, their atmosphere and formation and evolution processes, habitability and exobiology implications, and outlooks for future exploration and science development, including visionary contributions. Each section has 10-20 contributions written by the top experts in their subject, including both senior researchers as well as young, smart researchers who represent the future of the discipline. All in all, this handbook comprehensively tackles one of the most challenging and dynamic fields of modern astronomy and astrophysics. .